Records Committee review for rare bird sighting for Eskimo Curlew at Iowa before 1870 - Iowa Ornithologists' Union Records Committeeet al (1870)
Records Committee for Eskimo Curlews at Iowa before 1870. Includes a record review document with votes, the original sighting record found in the publication A Catalogue of the Birds of Iowa by J.A. Allen in Report on the Geological Survey of the State of Iowa by Charles A. White, and referenced by two other publications. Epson - sheet feed